Application of High-Sensitivity UV photoemission Spectroscopy to Examine the Electronic Structure of Thermophilic Rhodopsin. (3rd July 2019) - Sano, Daisuke; Ide, Ichiro; Akiyama, Tomoki; Tanaka, Yuya; Sudo, Yuki; Murata, Takeshi; Ishii, Hisao
Abstract: The electronic structures of materials such as HOMO and LUMO are essential information to understand their functions. Photoemission spectroscopy, which is the most standard technique to examine the electronic structures of various materials, has been not well applied to biomolecules mostly due to sample charging and poor sensitivity. Very recently, we have developed high-sensitivity photoemission spectroscopy (HS-PES) using low photon energy. In this study, HS-PES has been successfully applied to a thermophilic rhodopsin (TR) film. The high sensitivity of our technique enabled to observe the HOMO region of retinal part in TR without any problem due to sample charging. This technique is expected to explore the electronic structures of various proteins.